Cookware as source of toxic metals: An overview - Okunola Alabi; Amos Tomiwa Afolabi (Kashmir Journal of Science, 2024)
Cookware assumes a pivotal function in cooking, however, there are concerns about potential health hazards associated with the release of toxic metals into food. This review investigates importance of cookware as a source of exposure to toxic metals, with a focus on the health consequences of lead, cadmium and aluminum contamination. Certain materials used in cookware, especially metals, have been identified as potential origins of toxic elements. Lead, a well-known neurotoxin, can be released from cookware, presenting a risk when ingested. Cadmium in certain metal alloys and enamels, is another concern due to its toxicity, which affects various organs. Aluminum used in cookware, has raised health concerns because of its possible associations with neurodegenerative diseases. Metal leaching is influenced by various factors, including acidity, cooking duration, and temperature. Acidic foods, such as tomatoes or citrus fruits, can facilitate the release of metals into the food during the cooking process. Extended cooking times and high temperatures also increase the probability of metals migrating from the cookware into the food. Consumers need to make well-informed decisions when selecting cookware to mitigate these risks. Selecting materials with lower potential for metal leaching, such as stainless steel or cast iron, can significantly reduce exposure.